Reorientasi Strategi dan Tantangan Pembelajaran PAI Era Revolusi Industri 5.0: Reorientasi Strategi dan Tantangan Pembelajaran PAI - Firman Mansir; Achmad Ushuluddin; Anisa Rahmadani; Muhammad Yudi Ali Akbar; Abdullah Hakam Shah; Harmathilda Harmathilda (Journal of Innovative and Creativity, 2025)
This study aims to analyze new strategies in religious education in the digital age. The effectiveness and efficiency of learning are influenced by the accuracy of selecting the learning strategy. The research method employed is a qualitative approach, whereby data is collected through document searches to identify patterns of learning strategies. Analysis is then conducted using Holsti's content analysis, concluding the objective, systematic, and measurable identification of message characteristics. The results of the study confirm that religious education in madrasas has its own characteristics and methods for achieving learning objectives, so that PAI teachers must be able to determine the appropriate and effective models and strategies. In addition, the current learning effectiveness patterns are not yet fully effective, possibly due to a lack of creativity or new strategies to be applied during learning. The digital era has given rise to many learning systems that are conducted virtually and offline, which have a positive impact on the learning process, but also have a negative impact. This is due to several factors that hinder the virtual and offline learning process. Thus, in response to the advances of the digital era, religious education in madrasahs needs to develop new strategies for PAI teachers in implementing their teaching, with the aim and hope that learning can be carried out productively and effectively.